Hyperphosphatemia as a potential risk factor for arteriovenous fistula dysfunction: A retrospective study in hemodialysis patients - Yujie Jiang; Chengji Cui; He Nan; Tianying Chang; Fan Li; Shoulin Zhang (PLoS ONE, 2025)
Background The study investigates the relationship between Hyperphosphatemia and arteriovenous fistula dysfunction in patients undergoing maintenance hemodialysis. Methods Data were collected from patients who had their first arteriovenous fistula creation and regular maintenance hemodialysis between 2019 and 2023. Patients were divided into four groups based on serum phosphorus levels (<1.33 mmol/L, 1.33–1.61 mmol/L, 1.61–1.965 mmol/L, > 1.965 mmol/L). Statistical methods included Kaplan-Meier survival curves, Cox proportional hazards regression models, and Restricted Cubic Spline. Results The study included 239 patients. Kaplan-Meier survival curves showed that Hyperphosphatemia significantly correlated with arteriovenous fistula dysfunction (P = 0.0052). Cox univariate analysis showed phosphorus (HR = 3.16, P < 0.001) is risk factor of arteriovenous fistula dysfuntion. Multivariate Cox regression analysis further confirmed high phosphorus levels were an independent risk factor of AVF dysfuntion (P for trend<0.001). Restricted Cubic Spline showed a nonlinear relationship between phosphorus levels and arteriovenous fistula dysfunction (P for non-linearity = 0.024), with a cutoff point at 1.544 mmol/L (LR = 0.035). Conclusion Hyperphosphatemia is an independent risk factor for arteriovenous fistula dysfunction, emphasizing the need for clinical practice to pay attention to the impact of mineral metabolism disorders on the integrity of arteriovenous fistula and to strengthen phosphate management.